LEARNING COMMUNITY AS STRATEGY IN IMPROVING STUDENTS’ SPEAKING SKILL - Syarfuni (Jurnal Visipena, 2013)
The goal of this writing is to explore the learning speaking through learning community. Learning community is of element of contextual teaching and learning. Contextual teaching and learning (CTL) is approaches to be most effective in student learning, teachers must plan, implement, reflect upon, and revise lessons. Such plans are based on CTL principles and approaches that require teachers to serve in the following roles: facilitator, organizer of the teaching/learning/assessment process, role model, learning mentor, content specialist, and knowledge dispenser. A learning community is a model of teaching and learning that has been consistently shown to improve students’ speaking. The reason why learning community can enhance the students’ in expressing idea because it has the meaning as follows: 1).Group of learning which communicate to share the idea and experience, 2).Working together to solve the problem and 3).The responsibility of each member of learning group.